God Emperor of Dune [compact disc, unabridged] - Herbert, Frank (Herbert, Frank. Dune chronicles, 2008)
Leto II, God Emperor of Dune, trades his humanity for immortality and, as the magnificent sandworm of Dune, desperately attempts to save humankind.